Corn Cob Waste: A Sustainable Solution for Eco-Friendly Packaging: Limbah Tongkol Jagung: Solusi Berkelanjutan untuk Kemasan Ramah Lingkungan - Salsabila, Nisrina Khoirunnisa; Ambarani, Siti Maryam; Triana, Uut Ela; Rahmi, Yasmin Aulia; Sari, Fitri Ayu Puspita; Setiawati, Indah (Indonesian Journal of Innovation Studies, 2023)
This study investigates the market potential and competitive advantages of utilizing corn cob waste for environmentally-friendly packaging fillers. Employing a descriptive-analytical approach, Google Trends data is harnessed for analysis, complemented by competitor mapping to assess market competition. The findings demonstrate a promising market outlook for eco-friendly packaging products, both domestically and internationally, highlighting consumer behavior patterns in the decision-making process. This research underscores the viability of corn cob waste as a sustainable resource for innovative packaging solutions, with far-reaching implications for environmentally-conscious industries worldwide. Highlight: Sustainable Packaging Innovation: This study explores the viability of repurposing corn cob waste for eco-friendly packaging fillers, offering a sustainable alternative to conventional materials. Comprehensive Analytical Approach: Employing a descriptive-analytical methodology and leveraging Google Trends data, the research provides a thorough assessment of market potential and competitive advantages in the eco-friendly packaging industry. Global Implications for Sustainable Industries: The findings highlight a promising market outlook both domestically and internationally, emphasizing consumer behavior as a key factor in driving the adoption of eco-conscious packaging solutions. This research advocates for the widespread adoption of corn cob waste as a valuable resource for sustainable packaging innovations worldwide. Keyword: Eco-Friendly Packaging, Corn Cob Waste, Market Potential, Competitive Advantages, Sustainable Resource